Recovery‐oriented practice in a hospital mental health service - Lorien, Leonie M.; Arthur, Michael; Keiler, Katherine; Lowry, Joanne; Ryan, Kathleen (International journal of mental health nursing, 2024)
As part of mental health reform in Australia, new policies were introduced to support recovery‐oriented practice; however, little has changed in hospital settings focused on managing risk and remediating acute symptoms. Previous studies have indicated that patients' experiences of personal recovery, during a hospital admission, may not mirror that of people living in the community, with patients being more likely to experience disconnection, hopelessness and disempowerment. Using a Participatory Health Research approach, eight mental health professionals, a patient advocate and an external researcher formed a research partnership to answer the question: How can staff enhance recovery‐oriented practice in a hospital‐based mental health service? The COREQ checklist was used for reporting the methods, analysis and findings. The methods comprised patient focus groups (n = 16 participants), interviews with managers (n = 7) and an online survey for staff (n = 17). Researchers analysed the feedback from the consultations using inductive thematic analysis, identifying two themes: relational recovery and recovery interventions. The findings indicate that relational recovery is key to recovery during a hospital admission and interventions that increase connectedness or reduce the impact of symptoms enhance personal recovery.